Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.18632/aging.101468
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-506-3p inhibits osteosarcoma cell proliferation and metastasis by suppressing RAB3D expression

Abstract: Osteosarcoma is an aggressive bone tumor primarily affecting children and adolescents. Its cause is not yet fully understood, and there is an urgent need for more effective treatment. In the present study we identified several miRNAs whose expression is altered in osteosarcoma compared to adjacent normal tissue. Moreover, expression levels of one of those miRNAs, miR-506-3p, correlated negatively with expression of RAB3D (a Ras-related protein). Suppression of miR-506-3p in osteosarcoma led to increased expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…RAB3D involvement has been implicated in multiple regulatory processes, such as vesicle transport, protein secretion, and signal transduction (63,64). It was reported that RAB3D is highly expressed in tumor tissues and cells, and promotes the migration and invasion of tumor cells (65,66). In our study, we found that RAB3D can act as an oncogene in glioma, and hsa_circ_0088732 can regulate RAB3D expression by sponging miR-661.…”
Section: Discussionsupporting
confidence: 54%
“…RAB3D involvement has been implicated in multiple regulatory processes, such as vesicle transport, protein secretion, and signal transduction (63,64). It was reported that RAB3D is highly expressed in tumor tissues and cells, and promotes the migration and invasion of tumor cells (65,66). In our study, we found that RAB3D can act as an oncogene in glioma, and hsa_circ_0088732 can regulate RAB3D expression by sponging miR-661.…”
Section: Discussionsupporting
confidence: 54%
“…miRNAs are important regulators for tumorigenesis and it was proved that miRNAs have the potential to be used as novel therapeutic methods for cancer (10)(11)(12)(13)15). Rab3D, one member of the Rab GTPase family, serves an oncogenic role in several cancer types including osteosarcoma, esophageal squamous cell carcinoma and CRC (16)(17)(18). Evidence demonstrated that Rab3D is a key player in regulating tumor metastasis, which suggested that silencing Rab3D expression may be a way to restrain cancer metastasis (19).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wu et al revealed that MiRNA-145-3p was reported as a tumour suppressor, inhibiting proliferation and induces apoptosis and autophagy of OS cell [20]. miR-506-3p is a tumour suppressor by repressing the proliferation and metastasis of OS cell [21]. miR-223-3p was reported to suppress OS metastasis by targeting CDH6 [19].…”
Section: Introductionmentioning
confidence: 99%